Внесок І.Г. Шовкопляса у розробку питань економічної та суспільної організації пізньопалеолітичного населення півночі України - Кухарчук, Ю. (Археологія, 2002)
У статті подано оцінку ролі видатного українського археолога І.Г. Шовкопляса у відтворенні за археологічними джерелами господарського та соціального устрою первісних колективів, які населяли у пізньому палеоліті північні території України. В статье дана оценка вклада выдающегося украинского археолога И.Г. Шовкопляса в решение проблемы воссоздания образа жизни позднепалеолитических сообществ севера Украины. Главное внимание уделено разработанной ученым концепции хозяйственно-бытового комплекса, а также его исследованиям искусственных долговременных жилищ с точки зрения реконструкции общественного устройства их обитателей. The paper evaluates the contribution of the prominent Ukrainian archaeologist І.G. Shovkoplyas to the solution of the problem of reconstruction of the way of life of the Upper Paleolithic communities of Northern Ukraine. The main attention is paid to the conception of the economic-domestic complex elaborated by the scholar, as well as to his studies of man-made long-term dwellings from the viewpoint of reconstruction of the social organization of their inhabitants.